1996
DOI: 10.1021/ie950402t
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Aggregation of Polymorphs in Continuous Precipitation. 2. Kinetics of CaCO3 Precipitation

Abstract: Experiments with the continuous precipitation of calcium carbonate are reported in this study. Particle size distributions were measured on-line and interpreted by means of the simultaneous nucleation and the transformation models developed in part 1 of this sequence. Three regimes of precipitation are reported in this study, governed by the supersaturation and liquid phase [Ca2+]/[CO3 2-] ionic ratio. These comprise of a heterogeneous regime involving calcite and vaterite nucleation at moderate [Ca2+]/[CO3 2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
50
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 31 publications
6
50
0
Order By: Relevance
“…They reported that increasing the agitation speed of the precipitation It is easily shown that the average particle size decreased as Ca 2+ 0 increased, reaching a size of 25 nm at 0.2 M of calcium ions. This could be explained by the supersaturation level S as defined by Equation (5) and the concentration ratio Ca 2+ t CO 2− 3 t of calcium and carbonate ions involved in the reaction medium at a given precipitation time as reported by Chakraborty and Bhatia (1996) when they described the liquidphase supersaturation for precipitation of CaCO 3 :…”
Section: Resultsmentioning
confidence: 98%
“…They reported that increasing the agitation speed of the precipitation It is easily shown that the average particle size decreased as Ca 2+ 0 increased, reaching a size of 25 nm at 0.2 M of calcium ions. This could be explained by the supersaturation level S as defined by Equation (5) and the concentration ratio Ca 2+ t CO 2− 3 t of calcium and carbonate ions involved in the reaction medium at a given precipitation time as reported by Chakraborty and Bhatia (1996) when they described the liquidphase supersaturation for precipitation of CaCO 3 :…”
Section: Resultsmentioning
confidence: 98%
“…However understanding of the precipitation mechanism is still lacking at the higher supersaturations. Early models to describe the precipitation paths consider the nucleation of different polymorphs and hydrates, which then transform into more stable modifications 17,18 that can also be influenced by the presence of additive molecules. 19,20 New characterization tools such as cryogenic-TEM (cryo-TEM) or X-ray microscopy demonstrate the precipitation starts with particles ∼30 nm in size, which then transform into calcite or vaterite phases, [21][22][23][24] probably via agglomeration mechanisms involving amorphous calcium carbonate prenucleation clusters.…”
Section: Introductionmentioning
confidence: 99%
“…That is why, a kinetic model should account for their simultaneous presence in the solution (Chakraborty & Bhatia, 1996). Usually, because of the complexity and difficulty of such calculations, the considerations are limited only to calcite.…”
Section: Bubble Column Reactormentioning
confidence: 99%